Understanding econometrics - Stewart, Jon (London : Hutchinson, 1976)
The book covers: The two variable linear model; The linear model with further explanatory variables; Alternative disturbance specification; Distributed lags and dynamic economic models; Simultaneous equations models.
With answers.
Includes bibliographical references : p. 227and index.
rpm 22/09/2017
Loans
Keywords: Econometrics